Diagnostic performance and reference values of novel biomarkers of paediatric heart failure. Issue 20 (24th May 2016) - Hauser, Jakob A; Demyanets, Svitlana; Rusai, Krisztina; Goritschan, Clara; Weber, Michael; Panesar, Dilveer; Rindler, Lisa; Taylor, Andrew M; Marculescu, Rodrig; Burch, Michael; Wojta, Johann; Michel-Behnke, Ina
Abstract : Objective: Biomarkers play a pivotal role in heart failure (HF) management. Reference values and insights from studies in adults cannot be extrapolated to the paediatric population due to important differences in pathophysiology and compensatory reserve. We assessed the diagnostic utility of four novel biomarkers in paediatric HF. Methods: Midregional (MR) pro-atrial natriuretic peptide (proANP), soluble ST2 (sST2), growth differentiation factor-15 (GDF-15), MR-pro-adrenomedullin (proADM) and N-terminal pro-B natriuretic peptide (NT-proBNP) were measured in 114 patients and 89 controls. HF was defined as the presence of HF symptoms and/or abnormal systolic ventricular function. Receiver-operating characteristics were plotted, and the area under the curve (AUC) was measured. This was repeated for subgroups with cardiomyopathy and congenital heart disease (CHD). Ventricular systolic function was measured by magnetic resonance or echocardiography. Reference values were calculated according to the current guidelines. Results: The AUC for diagnosing HF was 0.76 for MR-proANP (CI 0.70 to 0.84) and 0.82 for NT-proBNP (CI 0.75 to 0.88). These parameters performed similarly in the subgroups with CHD and cardiomyopathy. By contrast, MR-proADM, GDF-15 and sST2 performed poorly. When used in conjunction with NT-proBNP, no parameter added significantly to its diagnostic accuracy. NT-proBNP, MR-proANP, GDF-15 and sST2 could accurately discriminate between patients with preserved and patients with poor functional status. In a subset of patients with dilated cardiomyopathy, NT-proBNP, MR-proANP, MR-proADM and GDF-15 were associated with poor LV function. Conclusions: MR-proANP could accurately detect HF in children and adolescents. Its diagnostic performance was comparable with that of NT-proBNP, regardless of the underlying condition. Reference values are presented.